Theoretical investigation on the optimal contracting for directors holding multiple directorships - Guoyu Lin; Anna Brown (Journal of Risk and Financial Management, 2022)
This paper is the first (to our knowledge) to analytically model the optimal contracting for a member of the board of directors who holds multiple directorships. Prior literature has found conflicting evidence on the overall effect of multiple directorships on shareholder welfare: busy board members are usually detrimental to firm operating performance due to the limited time and effort they are able to devote to each board; however, multiple directorships can be beneficial to firms if the board members gain knowledge and expertise through their multiple appointments. The objective of our study is to expand the research on the effects of multiple directorships on shareholder welfare by modeling the relationship between optimal incentives (pay-performance sensitivity) and the number of directorships. Modeling within the Linear-Exponential-Normal framework, and solving using Subgame-Perfect Nash Equilibrium, we find that this relationship is positive when efforts across directorships are either substitutive or complementary, which highlights another potential significant downside to multiple directorships: companies need to offer high incentive-based pay to compete for directors' efforts, leading to high-risk premia and welfare loss to shareholders. Our results may be of interest to policy makers considering setting limits on the number of board seats that may be held by directors at public companies, as well as shareholders considering appointing directors with multiple appointments.
Keywords: 650; board of directors; busy directors; incentive pay; optimal contracting